Overcoming Confidence Problems in Speaking English for Social Communication - Alviansyah, Luthfan; Hidayat, Didin Nuruddin; Mulyati, Yatni Fatwa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Individuals often lose confidence in learning and using English due to lack of support or even ridicule from the surrounding environment. In previous research, we found that quite a few people did not understand the importance of English in social life and were more focused on solving problems in the environment, not starting from facing these problems themselves. Through this case we want to change the way an individual thinks about being afraid of the things they face during the learning process, and we want to raise self-confidence in people out there who are learning English. The researcher used a qualitative method, using interviews involving 10th and 11th grade students at SMAN 1 Cileungsi (5 participants at each grade with a total of 10 participants). Based on the data analysis, it was found that many of the students who were studying English had problems with their self-confidence.